Spontaneous luxation frequency dependence of the «capsule bag-IOL» complex on the material and weight of the lens - A.A. Ivanov; O.P. Mishchenko; T.N. Iureva (Офтальмохирургия)
Relevance. Spontaneous luxation of the «capsule bag– IOL» complex in the long-term postoperative period is a serious complication. The search for regulated risk factors, the limitation of which will reduce the frequency of this complication, is relevant. Purpose. To evaluate association between frequency of spontaneous luxation of the «capsule bag – IOL» complex and the number of surgeries, taking into account the characteristics of the lens. Material and methods. 69 IOLs from 14 medical companies and 2 capsule rings were examined. The weight was determined using trusted torsion scales (accuracy ± 1 mg) under hydration conditions. IOLs were divided into 3 groups: ≤18 D; 18.5–24.0 D; ≥24.5 D. A retrospective analysis of 159 cases of spontaneous IOL luxation into the vitreous body over 13 years (2007–2020) was carried out. Comparison of IOL implantation results/luxation was carried out from 2006 to 2010, taking into account luxations from 2007 to 2020. Additionally, the number of years from IOL implantation to spontaneous luxation, the axial length of the eye, and the presence of pseudoexfoliation syndrome were evaluated. Results. A multiple excess of the weight of hydrophilic compared with hydrophobic IOLs was found in three comparison groups with a comparable refractive power (p=0.0001). Hydrophilic lenses in various groups were 1.5–1.82 times heavier than hydrophobic lenses. Spontaneous luxation of hydrophobic IOLs occurred less frequently by 11.86–49.22% compared to lenses made of hydrophilic materials. Conclusion. The weight of the IOL may play an important role in the pathogenesis of dislocation of the artificial lens. In the future, it is possible to develop recommendations to reduce the risk of luxation of the «capsule bag – IOL» complex in the long term for patients with an initial combination of non-correctable risk factors complicating the condition of the ligamentous apparatus of the lens.